Microwave irradiation synthesis of carbon nanotubes: advances, purification techniques, and scalability prospects / Muhamad Nor Iqmal Hafizi Kamaruddin ... [et al.] - Kamaruddin, Muhamad Nor Iqmal Hafizi; Idris, Siti Shawalliah; Kadri, Atikah; Abu Bakar, Noor Fitrah (Universiti Teknologi MARA, 2024)
Carbon nanotubes (CNTs) has been a subject of extensive research and development due to their exceptional properties. This article provides an overview of CNT production techniques, focusing on conventional methods such as arc discharge and chemical vapor deposition (CVD), as well as the emerging alternative, microwave (MW) irradiation technique. The MW irradiation technique offers a promising alternative with potential advantages in terms of energy efficiency and economical aspect. The article also discusses various purification techniques, mainly categorised into chemical and physical purification, underlining their advantages and challenges. Scalability of these production methods are also extensively discussed to explore the potential for scaling up MW irradiation technique, suggesting new alternative for achieving cost-effective and high-quality CNT production on an industrial scale. This review aims to provide insights into the current state of CNT production advancement and identify future opportunity for research and development in this field.